1985
DOI: 10.1021/bi00345a041
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteins as reverse micelles: myelin basic protein in a membrane-mimetic environment

Abstract: The solubility, reactivity, and conformational dynamics of myelin basic protein (MBP) from bovine brain were studied in reverse micelles of sodium bis(2-ethylhexyl) sulfosuccinate (AOT)-isooctane and water. Such a membrane-mimetic system resembles the aqueous spaces of native myelin sheath in terms of physicochemical properties as reflected in the high affinity of MBP for interfacial bound water. This is marked by the unusual profile of the solubility curve of the protein in reverse micelles, which shows optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 49 publications
5
70
1
Order By: Relevance
“…At a low degree of complexity, reverse micelles constitute a good membrane-mimetic system (Nicot et al, 1985;Leodidis and Hatton, 1990) for the study of the complex physicochemical forces acting at interfaces of multicomponent assemblies (Israelachvili and McGuiggan, 1988). The large size (66.5 kDa) and the number of amino acids (585) in HSA provide the opportunity for multiple protein-micellar surface interactions which would contribute to the process of conformational changes described herein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At a low degree of complexity, reverse micelles constitute a good membrane-mimetic system (Nicot et al, 1985;Leodidis and Hatton, 1990) for the study of the complex physicochemical forces acting at interfaces of multicomponent assemblies (Israelachvili and McGuiggan, 1988). The large size (66.5 kDa) and the number of amino acids (585) in HSA provide the opportunity for multiple protein-micellar surface interactions which would contribute to the process of conformational changes described herein.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction of N-bromosuccinimide with Trp214 was carried out in aqueous and micellar solutions as previously described by Nicot et al (1985). The course of tryptophan oxidation reaction was followed by the decrease in fluorescence emission (Privat et a1.,1976).…”
Section: Chemical Modifications Of Albuminmentioning
confidence: 99%
See 1 more Smart Citation
“…The polar heads of the surfactant molecules are directed toward the interior of a water-containing sphere, whereas the aliphatic tails are oriented toward the non-polar organic phase. The water structure within the reverse micelles may resemble that of water adjacent to biological membranes (Boicelli et al 1982), and it has been suggested that the reverse micellar system reliably mimics the microenvironment that enzymes encounter in the intracellular milieu (Nicot et al 1985, Luisi et al 1988, O'Connor and Wiggins 1988, Faeder and Ladanyi 2000.…”
Section: Introductionmentioning
confidence: 99%
“…At first glance, it might be expected that the enzyme would be more active in water with properties closer to those found in the surface of membranes. The extrinsic membranous myelin basic protein, for example, is preferentially solubilized in bound water (Nicot et al, 1985). The fact that the El conformer and, hence, the enzymatic turnover, needs bulk water, suggests that the catalytic site in that conformation is shielded from the membranous surface, either in the interior of the protein or projected to the cytoplasmic portion of the enzyme.…”
Section: Discussionmentioning
confidence: 99%